Managing plantar fasciopathy and tendinopathy through conditioning and load monitoring within elite sport. - Thompson, R. C. (Journal of Australian Strength and Conditioning, 2017)
There is strong evidence for managing Achilles tendinopathy or plantar fasciopathy through load management and conditioning protocols. This case presentation demonstrates a 25- year old elite female triathlete who was medically diagnosed 4 months before with a left plantar fasciopathy and mild mid portion Achilles tendinopathy. The athlete reported no previous tendinopthies during her triathlon or running career. Weekly load monitoring of running volume, via a GPS watch linked to Training Peaks software, was implemented alongside a comprehensive tendon loading program. Conditioning programs included a progressive overload of the kinetic chain targeting functional strength and energy storage release capacity over a period of 3 months. Specific focus was given to a multifactorial progressive heavy tendon loading program incorporated into the conditioning program. This was modified according to the athlete`s reported symptoms and the tendon`s load capacity. The athlete completed a maintenance tendon loading program the following season to assist in maintaining an injury free condition while continuing to compete at an elite level. This case presentation highlights the importance of a proactive integration between strength and conditioning coaches and the medical team. It offers suggestions how to use this integrated approach to manage lower limb tendinopathies with performance optimising outcome within high load elite level training.